2005
DOI: 10.1128/jcm.43.8.4083-4091.2005
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Diversity among Type emm28 Group A Streptococcus Strains Causing Invasive Infections and Pharyngitis

Abstract: Genome sequencing of group A Streptococcus (GAS) has revealed that prophages account for the vast majority of gene content differences between strains. Serotype M28 strains are a leading cause of pharyngitis and invasive infections, but little is known about genetic diversity present in natural populations of these organisms. To study this issue, population-based samples of 568 strains from Ontario, Canada; Finland; and Houston, Texas, were analyzed. Special attention was given to analysis of variation in prop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
48
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 56 publications
(48 citation statements)
references
References 55 publications
0
48
0
Order By: Relevance
“…Since sequence similarities do not include the cysteine residue in position 257, these data imply that Mac-2 M28 represents a unique Mac-2 variant favoring receptor binding properties before IgG endopeptidase activity. Although streptococcal strains of the M1 serotype are currently most frequently associated with invasive streptococcal disease (e.g., see references 3, 8, and 15), M28 serotype strains are repeatedly reported as the leading cause of invasive and noninvasive disease (3,9,11,15,17). It is tempting to speculate whether the evolution (or preservation) of Mac M28 correlates with the reemergence of M28-associated pathogenesis: i.e., the prevalence of M28 serotypes in puerperal sepsis and/or neonatal infections (9).…”
Section: Discussionmentioning
confidence: 99%
“…Since sequence similarities do not include the cysteine residue in position 257, these data imply that Mac-2 M28 represents a unique Mac-2 variant favoring receptor binding properties before IgG endopeptidase activity. Although streptococcal strains of the M1 serotype are currently most frequently associated with invasive streptococcal disease (e.g., see references 3, 8, and 15), M28 serotype strains are repeatedly reported as the leading cause of invasive and noninvasive disease (3,9,11,15,17). It is tempting to speculate whether the evolution (or preservation) of Mac M28 correlates with the reemergence of M28-associated pathogenesis: i.e., the prevalence of M28 serotypes in puerperal sepsis and/or neonatal infections (9).…”
Section: Discussionmentioning
confidence: 99%
“…1). With respect to these variables, the work of Green et al, which is the only study directly comparable to the present one, even if restricted to emm28 GAS, reported an m vir equal to 3.6 and an overall number of 46 profiles (12). Only 50 strains analyzed here could be classified in just 11 profiles represented in the scheme of Green et al…”
mentioning
confidence: 73%
“…All isolates of the two outbreak types were analyzed for amplification of speA, speB, and speC genes using the primers speA-fw (5Ј-ACT TAA GAA CCA AGA GAT GG-3Ј) and speA-rev (5Ј-CTT TAT TCT TAG GTA TGA AC-3Ј), speB-fw (5Ј-GTC AAC ATG CAG CTA CAG GA-3Ј) and speB-rev (5Ј-AAT ACC AAC ATC AGC CAT CA-3Ј), and speC-fw (5Ј-TCT AGT CCC TTC ATT TGG TG-3Ј) and speC-rev (5Ј-GTA AAT TTT TCA ACG ACA CA-3Ј), respectively, as reported previously (11,30). The PCR cycle used for amplification was as follows: denaturation at 94°C for 15 s, annealing at 55°C for 30 s, extension at 72°C for 1 min for 30 cycles, and a final extension at 72°C for 5 min.…”
Section: Methodsmentioning
confidence: 99%